Extended-cavity optical sources with modulation averaging reflectors : doctoral thesis - Komljenović, Tin 1982 (T. Komljenović ; Fakultet elektrotehnike i računarstva, 2012)
Passive optical networks with wavelength multiplex (WDM-PON) allow high speed transmission in access networks, but have not yet been widely deployed primarily due to cost. Wavelength-agnostic transceivers at the user end in colorless WDM-PON systems offer significant cost reduction as each of the optical network units is identical. The cost and complexity of the system is further reduced by using self-seeded WDM-PON architectures in which a reflector at a remote node allows the amplified-spontaneous-emission signal emitted from the reflective semiconductor optical amplifier to seed itself. A new component is introduced in self-seeded systems, an averaging reflector, and it is demonstrated that the link margin in such systems can be further improved by it. The modulation-averaging reflector changes the amplitude probability density distribution of the modulated seeding light from a sharply bound distribution into a near-normal distribution which then alters the error statistics and results in improved performance. Most importantly, the modulation-averaging reflector is a passive optical device and therefore the remote nodes in our proposed WDM-PON system remain passive, with no power needed to accomplish this improvement. -